Appraisal of traditional African social welfare practices. a review of things fall apart (2013)
The paper briefly explains the concepts of African social welfare system and the present formal social welfare. It expounds on traditional charity and traditional means of meeting human needs in Africa before the coming of the Europeans. We examined the novel, "Things Fall Apart", to exemplify indigenous social welfare system. The study establishes the existence of well organised social welfare that pre-dates colonialism in traditional African society and the importance of the welfare system to individuals and the community in general. In addition, the paper gives an appraisal of mutual aids as described in the novel, relating it to the traditional African welfare system and its relevance and position in contemporary welfare system. The paper concludes that the concept of social welfare had been part of traditional African society before the advent of colonialism and calls for more research in order to identify notable African customs and practices as portrayed in African literature.